2012
DOI: 10.1051/epjap/2012110311
|View full text |Cite
|
Sign up to set email alerts
|

Polycrystalline silicon thin films on glass deposited from chlorosilane at intermediate temperatures

Abstract: We show that commercial float glass can be used as a substrate to deposit polycrystalline silicon (poly-Si) by chemical vapor deposition from trichlorosilane at temperatures between 740 and 870 • C. By using scanning electron microscopy an average grain size lower than 0.4 μm was observed, with a columnar structure suitable for the electrical conduction in photovoltaic cells. X-ray diffraction reveals a strong (2 2 0) preferential orientation of the films, which is indicative of a low density of intra-grain de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…The basic structural characterization of the films has been presented in [7]. As a summary, we can say that the films are dense and uniform, with a good coverage and adhesion to the substrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic structural characterization of the films has been presented in [7]. As a summary, we can say that the films are dense and uniform, with a good coverage and adhesion to the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous work [7], we have shown that a commercial aluminosilicate glass (Schott AF37 [8]) can be used as a substrate to deposit poly-Si by AP-CVD from SiHCl 3 at intermediate temperatures between 735 and 870 • C. By using boron tribromide (BBr 3 ) as a doping agent, degrees of doping ranging from intrinsic to clearly p-doped were obtained. The structural properties of the films were evaluated by means of scanning electron microscopy (SEM), atomic force microscopy (AFM), x-ray diffraction and reflectance in the ultraviolet region.…”
Section: Introductionmentioning
confidence: 99%
“…The average grain size is about 190 nm, independent of the BBr 3 concentration. Within the doping range of our experiments, this average grain size is lower than that of undoped samples (around 270 nm) deposited with the same procedure and the same parameters . This means that the addition of boron increases the nucleation rate.…”
Section: Resultsmentioning
confidence: 50%
“…TLS reduces at high temperature in the presence of hydrogen, resulting in the deposition of silicon and the release of hydrochloric acid. This reaction is reversible, meaning that, under certain circumstances, hydrogen chloride can etch the silicon deposited . Boron tribromide or phosphorous trichloride also reduce in the presence of hydrogen, leading to the incorporation of boron or phosphorous into the silicon lattice, and the release of hydrobromic or hydrochloric acid, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation